Navigating Hostile Workplaces and Educational Spaces Within Health Services and Policy Research - Taylor B. Rogers; Kevin Q. Graham; Carmen R. Mitchell; Tongtan Chantarat; Michelle J. Ko (Health Equity)
Introduction: The representation of ethnoracial minoritized individuals in health services and policy research (HSPR) has increased in recent years. However, previous literature has exposed a need to acknowledge and attend to inequities within the HSPR workforce. Methods: To describe educational and workplace experiences that characterize diversity, equity, and inclusion (DEI) within the HSPR profession. In this qualitative study, six focus groups were conducted virtually via Zoom with 27 individuals who reported working or pursuing higher education in HSPR from December 2020 to January 2021. We sought HSPRers perspectives on DEI initiatives, work and educational environments, experiences, and climate, and recommendations for improving DEI in HSPR. We developed a structured codebook and applied a deductive approach to conduct thematic analysis. Results: Of the 27 participants, nearly half of participants identified as Black/African American (44%); most were women (81%). Three major themes emerged: (1) HSPR work and education spaces subject minoritized HSPRs to a range of exclusionary and harmful practices; (2) DEI initiatives fail to address the need for institutional change; and (3) by working with and for policymakers, HSPRs are uniquely subjected to shifting political contexts that reinforce racism. Discussion: Despite an increasing commitment to increasing the diversity of the HSPR workforce and improving equity and inclusion in the HSPR workplace, the findings suggest that more intentional and action-oriented work is needed, especially work that emphasizes inclusion and equity across various levels of the workplace. Health Equity Implications: The findings offer critical insight on necessary workplace and educational reform to develop the workforce necessary to advance population health equity and equity-oriented policy making.